A review of production and upgrading of algal bio-oil. (May 2016) - Saber, Mohammad; Nakhshiniev, Bakhtiyor; Yoshikawa, Kunio
Abstract: Depletion of the oil reservoirs necessitates developing renewable fuels to replace petroleum-based fuels. Biomass-derived fuels with zero net CO2 emission are promising substitutes for fossil fuels. Bio-oil has been considered as an alternative energy source for fuel applications. At the present time, there are two principal processes for bio-oil production from biomass: pyrolysis and hydrothermal liquefaction. Pyrolysis requires drying of feedstock which increases the energy consumption of the process. On the other hand, hydrothermal liquefaction is conducted in aqueous environment which makes it suitable for aquatic plants and wet biomass. One of the main challenges in bio-oil application is the poor quality of the bio-oil. Bio-oil has undesirable properties such as high oxygen content and acidity which requires upgrading of the bio-oil for fuel application. This article reviews bio-oil production and upgrading techniques from algae (micro- and macro-algae). The chemistry and characteristics of bio-oil as well as recommendations for future works are also covered in this paper.